Neuronal activity in medial superior temporal area (MST) during memory-based smooth pursuit eye movements in monkeys - Kurkin, Sergei (Springer-Verlag, 2011)
We examined recently neuronal substrates for predictive pursuit using a memory-based smooth pursuit task that distinguishes the discharge related to memory of visual motion-direction from that related to movement preparation. We found that the supplementary eye fields (SEF) contain separate signals coding memory and assessment of visual motion-direction, decision not-to-pursue, and preparation for pursuit. Since medial superior temporal area (MST) is essential for visual motion processing and projects to SEF, we examined whether MST carried similar signals. We analyzed the discharge of 108 MSTd neurons responding to visual motion stimuli. The majority (69/108 = 64%) were also modulated during smooth pursuit. However, in nearly all (104/108 = 96%) of the MSTd neurons tested, there was no significant discharge modulation during the delay periods that required memory of visual motion-direction or preparation for smooth pursuit or not-to-pursue. Only 4 neurons of the 108 (4%) exhibited significantly higher discharge rates during the delay periods; however, their responses were non-directional and not instruction specific. Representative signals in the MSTd clearly differed from those in the SEF during memory-based smooth pursuit. MSTd neurons are unlikely to provide signals for memory of visual motion-direction or preparation for smooth pursuit eye movements.